Dysmenorrhea in adolescent girls: Does body mass index play a role? - Rifkiyatul Islami, Ica Maulina (Science Midwifery, 2024)
This study aims to analyze the relationship between Body Mass Index (BMI) and dysmenorrhea pain scale in female adolescents at SMP Nurul Jadid, Paiton District. Dysmenorrhea is one of the common complaints in female adolescents that often affects daily activities and academic achievement. BMI, which is an indicator of a person's nutritional status, is thought to be related to the severity of dysmenorrhea pain. By understanding this relationship, it is hoped that more effective treatment strategies can be developed to reduce dysmenorrhea pain based on the individual's physical condition. This study used an observational analytical method with a cross-sectional approach. The study sample consisted of 174 female adolescents who were randomly selected from SMP Nurul Jadid. Data collection was carried out through BMI measurements and dysmenorrhea pain scale questionnaires filled out by respondents. Data analysis was carried out using the Pearson correlation test to determine the relationship between BMI and dysmenorrhea pain scale. The results showed a significant negative correlation between BMI and dysmenorrhea pain scale in female adolescents (-698, p < 0.01). This indicates that the lower a person's BMI, the higher the level of dysmenorrhea pain experienced. Discussion of these results suggests that adolescent girls with higher BMI may experience increased levels of the hormone prostaglandin, which can increase the intensity of menstrual pain. In addition, lifestyle factors and dietary habits also have the potential to influence the relationship between BMI and dysmenorrhea pain. The conclusion of this study is that there is a negative relationship between BMI and the scale of dysmenorrhea pain in adolescent girls at SMP Nurul Jadid. This study suggests the need for special attention to nutritional status and healthy lifestyles to reduce dysmenorrhea pain in adolescent girls. Education on dysmenorrhea management involving lifestyle changes and weight management may be an effective step to help adolescents cope with dysmenorrhea better.